ANALISIS EFISIENSI PRODUKSI USAHATANI UBI KAYU DI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Maria Dhu’a Fitriana; Wan Abbas Zakaria; Eka Kasymir (Lampung University, 2019)
This study aims to analyze the profitability, factors that affect production and production efficiency of cassava farming. The research is conducted by survey method in Natar District of South Lampung Regency from June to August 2017. The 56 research samples are obtained by simple random sampling method. Primary data is obtained from direct questionnaires interview with cassava farmers and secondary data obtained from several related institutions. Data is analyzed qualitatively and quantitatively by income analysis and production function of Cobb Douglas. The results showed that cassava farming in Natar District of South Lampung Regency was profitable for farmers of Cassesart variety and not profitable for other varieties. Factors affecting cassava farming for respondents of Cassesart variety were land area, urea fertilizer and labor, for respondents of other varieties were land area and labor. Production process was not efficient and in increasing return to scale phase.Key words: cassava, efficiency, production, profit